Why has public transit ridership declined in the United States?. (July 2022) - Erhardt, Gregory D.; Hoque, Jawad Mahmud; Goyal, Vedant; Berrebi, Simon; Brakewood, Candace; Watkins, Kari E.
Graphical abstract: Highlights: Between 2012 and 2018, bus ridership in the US declined 15% and rail ridership declined 3%. We identify the factors responsible and quantify the contribution of each. Expanded transit service and land-use changes would have led to higher ridership but were offset by other factors. Ride-hailing is the biggest contributor to transit ridership decline. Higher fares, incomes, teleworking and car ownership, and lower gas prices also contribute. Abstract: Between 2012 and 2018, bus ridership in the United States declined 15% and rail ridership declined 3%. These losses are widespread and in contrast to trends in other countries. Using data from 215 Metropolitan Statistical Areas (MSAs) prior to the COVID-19 pandemic, we identify the factors responsible for this decline and quantify the contribution of each. We show that expanded transit service and land-use changes increased ridership 4.7% on bus and 10.7% on rail. However, losses due to other factors exceed these gains. Ride-hailing is the biggest contributor to transit ridership decline over this period, reducing bus ridership by 10%. Ride-hailing's effect on rail varies by metropolitan area size: it has little effect on rail ridership in the largest metropolitan areas but decreases rail ridership 10% in mid-sized metropolitan areas. Lower gas prices and higher fares contribute to lower transit ridership, as do higher incomes, more teleworking and higher car ownership. By providing a clear understanding of the causes of transit ridership decline, our research provides the foundation on which communities can craft an effective response to the problem.